MENYOAL GLOBAL SALAFISM: RAHMATAN ATAU LA’NATANLIL ‘ALAMIN? - Fera Andriani (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2018)
Study of Global Salafism is an issue that is being discussed in the vibrant is related to the abundance of tragedy and terror across the world, especially in post 911 attacks in America. Why Salafi Wahabi was considered responsible for the rampant terror action? What and how does the doctrine that their followers cultivated so that it becomes so loyal? A major study in this paper revolves around doctrine and the identity of the Salafi Wahabi, how they behave to the even other religions. Then proceed with the study surrounding the Salafi and how it relates to politics. Also discussed about the Jihadi Salafi, as well as its branches in the menggurita duniamelaluiperantaraan to the entire internet. Salafi movement then locally and globally, as well as how to create Islamic rahmatan li-l-' alamin. This study concludes with a summary and the link between Global Salafism with Islamic studies.